2013
DOI: 10.1080/08870446.2013.859258
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age and death awareness on intentions for healthy behaviours

Abstract: Terror management theory (TMT) suggests that people are motivated to distance themselves from death. One way of doing this is to report greater intentions to engage in health-promoting behaviours following increased awareness of mortality, also referred to as a proximal defense. Older adults' comparatively fewer remaining years and greater likelihood of having significant health problems may result in greater intentions to promote health following mortality reminders, but little is known about their proximal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…For instance, in the current study, strength and physical competence were a large part of the prostate cancer journey and goals for recovery. Given the emergence of the sub-theme entitled “Engagement in New Health Behaviours,” it is interesting how Bevan, Maxfield and Bultmann [ 40 ] suggest that with increasing proximity to mortality, adults over sixty significantly increase healthy behaviours in later life. This assertion supports how men with a prostate cancer diagnosis may engage in positive health behaviour changes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the current study, strength and physical competence were a large part of the prostate cancer journey and goals for recovery. Given the emergence of the sub-theme entitled “Engagement in New Health Behaviours,” it is interesting how Bevan, Maxfield and Bultmann [ 40 ] suggest that with increasing proximity to mortality, adults over sixty significantly increase healthy behaviours in later life. This assertion supports how men with a prostate cancer diagnosis may engage in positive health behaviour changes.…”
Section: Discussionmentioning
confidence: 99%
“…The Terror Management theory argues that human understanding of mortality creates an existential anxiety that must be kept under constant control. Defences are erected to keep thoughts about death as far removed from the consciousness as possible [ 42 , 43 ]. Not everybody can face their own death and write about it.…”
Section: Discussionmentioning
confidence: 99%
“…Starting with proximal defenses, studies assessing age differences yield mixed results. Whereas Taubman-Ben- Ari and Findler (2005) found that younger adults reported greater healthrelated intentions, and older adults reported lower healthrelated intentions after a mortality prime, Bevan, Maxfield, and Bultmann (2014) found that both younger and older adults responded to increased awareness of mortality with greater intentions to engage in health-promoting behavior. Differences in results likely relate to the age groups, as Taubman-Ben-Ari and Findler included individuals aged 51-65 (M age = 56.25) in their older adult group, and Bevan and colleagues' older adult sample ranged in age from 60 to 89 years old (M age = 72.98), a sample that may be more representative of older age, given current life expectancies.…”
mentioning
confidence: 89%